Gender differences on 10-year outcomes following ST-segment elevation myocardial infarction: a subgroup analysis from the examination extend trial. (3rd October 2022) - Gabani, R; Spione, F; Arevalos, V; Ortega, L; Brugaletta, S; Grima Sopesens, N; Sabate, M; Gomez Lara, J; Jimenez, M; Jimenez Quevedo, P
Abstract: Background: Short-term outcomes of women following STEMI are worse than men, with specifically a higher mortality rate. However, it is unknown if gender may play a role in long-term outcomes. We aim to assess whether very long-term outcomes following STEMI treatment may be still influenced by gender. Methods: The EXAMINATION-EXTEND study was an investigator-driven 10-year follow-up of the EXAMINATION trial, which randomly 1:1 assigned 1498 STEMI patients to receive either EES (n=751) or bare metal stent (BMS) (n=747). This is a sub-analysis of this study, according to gender. Primary endpoint was the composite patient-oriented endpoint (POCE, all-cause death, any myocardial infarction, or any revascularization) at 10-year. Secondary endpoints were individual components of the primary endpoint. All the endpoints were adjusted for age. Results: Out of 1498 STEMI patient, 254 (17%) were women. Overall, women were older, with more arterial hypertension and less smoking history than men. At 10-year, no difference was observed between women and men in terms of POCE (40.6% vs. 34.2%; adjusted hazard ratio (HR) 95% confidence interval [CI]1.14 [0.91–1.42], p=0.259). There was a trend toward a higher all-cause death in women vs. men (27.6%, vs. 19.4%; adjusted HR [95% CI] 1.30 [0.99–1.71], p=0.063), without difference in cardiac death. No differences were present in terms of the other endpoints. Conclusions: At very long-term follow-up there were no differences in the combined patient-oriented endpoint between women and men, with a trend towards a higher all-cause death in women. These findings may suggest that very long-term healthcare attention following STEMI in women should go beyond reduction of cardiac events. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Public hospital